Prophylactic intravitreal injection of aflibercept for preventing postvitrectomy hemorrhage in proliferative diabetic retinopathy: A randomized controlled trial - Qu, Jinfeng; Chen, Xiuju; Liu, Qinghuai; Wang, Fang; Li, Mingxin; Zhou, Qiong; Yao, Jin; Li, Xiaoxin (Frontiers in Public Health, 2023)
Introduction: To assess the effects of preoperative intravitreal aflibercept (IVA) injection on the incidence of postoperative vitreous hemorrhage (VH) after vitrectomy for proliferative diabetic retinopathy (PDR). Methods: This is a prospective, randomized clinical trial. 128 eyes of 128 patients of PDR underwent pars plana vitrectomy (PPV) were enrolled. 64 eyes were assigned randomly to either IVA group (IVA injection 1 to 5 days before PPV) or control group (no IVA injection). The primary outcome was the incidence of VH at one month after PPV. Secondary outcome measures were best-corrected visual acuity (BCVA) changes from baseline at 1 week, 1 month, 2 months and 3 months after surgery. Results: The VH incidences in IVA groups and control group were 14.8% and 39.3% at week 1, 8.6% and 31.7% at month1, 11.7% and 30.5% at month 2, 8.6% and 30.5% at month 3, respectively. Intergroup differences showed significantly decreased VH rate in IVA group compared with that of control group at week 1, month1, and month 3 (p=0.021, 0.006 and 0.047, respectively). Neither the mean BCVA or the BCVA change in logMAR scale comparing to baseline did not differ significantly between two groups at each visit point. There are a greater number of eyes with BCVA improvement more than 2 logMAR in IVA group than in control group at week 1 (8 vs. 2, p=0.048). Conclusions: This study found adjunctive use of preoperative IVA reduce early and late postoperative VH in vitrectomy for PDR.